Anatomy of Corpus Callosum in Prenatally Malnourished Rats - Hernandez-Kunstmann, A (2012)
The effect of prenatal malnutrition on the anatomy of the corpus callosum was assessed in adult rats (45-52 days old). In the prenatally malnourished animals we observed a significant reduction of the corpus callosum total area, partial areas, and perimeter, as compared with normal animals. In addition, the splenium of corpus callosum (posterior fifth) showed a significant decrease of fiber diameters in the myelinated fibers without changing density. There was also a significant decrease in diameter and a significant increase in density of unmyelinated fibers. Measurements of perimeter s fractal dimensions from sagittal sections of the brain and corpus callosum did not show significant differences between malnourished and control animals. These findings indicate that cortico-cortical connections are vulnerable to the prenatal malnutrition, and suggest this may affect interhemispheric conduction velocity, particulary in visual connections (splenium).